2013
DOI: 10.1080/02755947.2013.812582
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Movement among Different Populations of Cutthroat Trout Introduced as Embryos to Vacant Habitat

Abstract: Translocations are frequently used to increase the abundance and range of endangered fishes. One factor likely to affect the outcome of translocations is fish movement. We introduced embryos from five Westslope Cutthroat Trout Oncorhynchus clarkii lewisi populations (both hatchery and wild) at five different locations within a fishless watershed. We then examined the movement of age‐1 and age‐2 fish and looked for differences in movement distance among source populations and among introduction sites; we also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Consistent with prior studies (Symons ; Cresswell ; Weber and Fausch ; Andrews et al. ), we found that NOR fish dispersed greater distances, with an estimated median dispersal distance of NOR parr almost 200% greater than that of HOR fish (Figure ). In addition to the possible role of density‐dependent competition, we speculate that this pronounced difference may have been influenced by selection for sedentary habits in multigeneration segregated hatchery broodstocks (Einum and Fleming ), environmental differences between the egg boxes and natural redds (e.g., egg incubation temperature, food availability, interactions with resident fish, etc.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with prior studies (Symons ; Cresswell ; Weber and Fausch ; Andrews et al. ), we found that NOR fish dispersed greater distances, with an estimated median dispersal distance of NOR parr almost 200% greater than that of HOR fish (Figure ). In addition to the possible role of density‐dependent competition, we speculate that this pronounced difference may have been influenced by selection for sedentary habits in multigeneration segregated hatchery broodstocks (Einum and Fleming ), environmental differences between the egg boxes and natural redds (e.g., egg incubation temperature, food availability, interactions with resident fish, etc.…”
Section: Discussionsupporting
confidence: 90%
“…Translocation or managed relocation may be a management option for facilitating range shifts for species that are restricted in their ability to move in response to climate change or other threats (Lawler and Olden 2011). Preserving population structure and diversity by using wild, most-closely-related populations in translocation efforts is important (Metcalf et al 2007(Metcalf et al , 2012, but hatchery supplementation of native species may provide a viable alternative in some cases (Andrews et al 2013). In addition, high-quality habitat is important for successful reintroductions (Cochran-Biederman et al 2014), although a thorough assessment is warranted to ensure success (Perez et al 2012).…”
Section: Managing Pacific Trout Across Changing Landscapesmentioning
confidence: 99%
“…the study area. Here we provide a brief summary of that information and add details for methods not discussed by Andrews et al (2013).…”
mentioning
confidence: 99%
“…We introduced about 35,000 Cutthroat Trout embryos from five different source populations to two different sites during each of 3 years for a total of six distinct introduction sites ( Figure 1). We chose these introduction sites to (1) spread fish throughout the watershed, (2) include sites with different temperature regimes (Table 1), and (3) enable selection of suitable habitat for remote-site incubators (RSIs; Andrews et al 2013) to ensure embryo survival (e.g., rocky substrate to stabilize buckets and enough gradient to keep water consistently running through the incubators). The first two sites (Cherry Lake Creek and Cherry Creek) were the farthest upstream.…”
mentioning
confidence: 99%
See 1 more Smart Citation